1996
DOI: 10.1063/1.363766
|View full text |Cite
|
Sign up to set email alerts
|

Photoacoustic spectroscopy of diluted magnetic semiconductors

Abstract: The absorption coefficient of several diluted magnetic semiconductors was measured below the fundamental absorption edge of the pure host compound at room temperature using the photoacoustic technique. Several absorption bands have been detected and assigned to electronic transitions between the crystal field split 3d levels of the transition metal ion. In addition, weak absorption thresholds have been observed and assigned to the ionization of the transition metal d states. An energy level diagram of the d st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
12
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 29 publications
1
12
0
Order By: Relevance
“…It offers promising candidate for many applications in the areas of battery cathode [15], catalysis [16], gas sensors [17], magnetic materials [18], and p-type semiconductors with wide band gap energy of $4 eV [19]. Although NiO nanostructures have been synthesized by the hydrothermal method and the decomposition of Ni(OH) 2 [11,12,20], few researches have been done on optical and field emission properties of NiO nanostructures.…”
Section: Introductionmentioning
confidence: 99%
“…It offers promising candidate for many applications in the areas of battery cathode [15], catalysis [16], gas sensors [17], magnetic materials [18], and p-type semiconductors with wide band gap energy of $4 eV [19]. Although NiO nanostructures have been synthesized by the hydrothermal method and the decomposition of Ni(OH) 2 [11,12,20], few researches have been done on optical and field emission properties of NiO nanostructures.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, much attention has been focused on the research field of one-dimensional nanostructured materials, such as nanorods, nanowires, or nanofibres, because of their potential applications in nanodevices [3][4][5]. Nickel oxide (NiO) is a very important material extensively used in catalysis [6], battery cathodes [7,8], gas sensors [9], electrochromic films [10,11], and magnetic materials [12,13]. A few methods on the preparation of NiO nanocrystalline powder and films were reported [14][15][16].…”
mentioning
confidence: 99%
“…It is reported that the morphologies and size of the nanomaterials can influence their applications [5][6][7][8]. As a typical metal oxide, nickel oxide (NiO) has been insensitively investigated because of its applications as catalysts, electrode materials for lithium ion batteries and fuel cells, electrochromic films, electrochemical supercapacitors, and magnetic materials [9][10][11][12][13][14][15][16]. Recently, in order to impart greater control over material and device properties, NiO with different morphologies such as nonoparticles [17], nanorods [18], nanosheets [19] and microspheres [20] has been reported with the development of synthetic techniques of nanomaterials.…”
Section: Introductionmentioning
confidence: 99%